Predictive value of the pathological extent of tumor invasion in endoscopic resection margins positive for residual tumor cells in surgically resected specimens of early gastric cancer - TSUJIMOTO, HIRONORI (D.A. Spandidos, 2012)
Although endoscopic resection (ER) is considered to be the optimal treatment for early gastric cancer, indications for radical gastrectomy in patients undergoing incomplete ER for early gastric cancer remain unclear. We evaluated the pathological extent of tumor invasion in the ER margins positive for residual tumor cells in the surgically resected specimens. We measured the vertical and/or horizontal length of the exposed tumor in the ER specimens of 23 patients with margins positive for tumor cells. We compared the clinicopathological data to distinguish between the presence and absence of residual tumor cells in the surgically resected specimens. Of 17 lesions with exposed tumor cells in the vertical margins of the ER specimens, only 3 (17.6%) had residual tumor cells in the corresponding site of the surgically resected specimens. By contrast, of 10 lesions with exposed tumor cells in the horizontal margins of the ER specimens, 8 (80.0%) had residual tumor cells in the corresponding site of the surgically resected specimens. The length of the exposed tumor in the vertical margins of the ER specimens was significantly associated with the incidence of residual tumor cells in the vertical margins of the surgically resected specimens. When the cut-off value for the length of the exposed tumor in the vertical ER margins was set to >3 mm, the sensitivity and specificity were 0.67 and 0.95, respectively. In conclusion, measurement of the length of the exposed tumor in the ER margins for early gastric cancer is a simple procedure that is able to determine whether additional surgical intervention is necessary.